Early‐Time GPR: A Method to Monitor Spatial Variations in Soil Water Content during Irrigation in Clay Soils. Issue 11 (3rd November 2016) - Algeo, Jonathan; Van Dam, Remke L.; Slater, Lee
Abstract : Core Ideas: Early‐time analysis extends the use of GPR to attenuating, clay‐rich soils. Early‐time GPR can upscale point measurements of water content when calibrated. Ongoing work studies alternative statistics to represent the early‐time signal. We used a recent ground‐penetrating radar (GPR) methodology, early‐time amplitude analysis, with the goal of monitoring changes in soil water content (SWC) in response to irrigation in clayey soils. We hypothesized that early‐time analysis could be used to monitor changes in SWC in clay‐rich soil where ground wave and reflection‐based GPR methods traditionally fail. An overnight irrigation experiment was performed in a 20‐ by 14‐m section of natural grassland at the Samford Ecological Research Facility in southeastern Queensland, Australia. Both GPR reflection surveys and ground wave velocity analysis were ineffective at the site due to the signal attenuation associated with the clay‐rich soil. We collected daily GPR and time‐domain reflectometry (TDR) data sets during a 5‐d period in August 2014, with soil samples collected for gravimetric analysis at the conclusion of data collection. The GPR data display a clear response of the early‐time signal amplitude to changes in SWC. The GPR data sets exhibit a strong correlation with SWC, as measured by TDR and gravimetric analysis of soil cores, which is consistent with the dependence of GPR early‐time amplitude on relative permittivity. The results suggest that the early‐time method can be used to obtain spatially distributed information on subsurface moisture content in clay‐rich soils.